2014
DOI: 10.1097/aog.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Cerebral White Matter Lesions Years After Preeclampsia and Eclampsia

Abstract: White matter lesions are more common in women with prior pregnancies complicated by preeclampsia or eclampsia compared with parous women in a control group. In no group does regional white matter lesion distribution correspond to the occipitoparietal edema distribution seen in posterior reversible encephalopathy syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 28 publications
(42 reference statements)
4
64
2
2
Order By: Relevance
“…Subsequent studies suggested greater white matter lesion burden five to seven years after the affected pregnancies. 11-14 Our study suggests even longer-term adverse effects of hypertensive pregnancies, such that these affected women have greater brain atrophy decades after their pregnancies compared to women who had normotensive pregnancies. There was also a trend for white matter lesions.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Subsequent studies suggested greater white matter lesion burden five to seven years after the affected pregnancies. 11-14 Our study suggests even longer-term adverse effects of hypertensive pregnancies, such that these affected women have greater brain atrophy decades after their pregnancies compared to women who had normotensive pregnancies. There was also a trend for white matter lesions.…”
Section: Discussionmentioning
confidence: 76%
“…11-14 For example, previous neuroimaging studies in women with severe forms of preeclampsia demonstrated significant white matter lesions. 11 Neuroradiological abnormalities, in the form of vasogenic edema at the time of delivery, persisted in a few patients up to eight weeks postpartum, presumably caused by gliosis in response to infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that long-term changes may occur within the brains of women with a history of preeclampsia. In long-term studies of women with a history of preeclampsia or eclampsia, 34–37% and 41% respectively were found to have white matter lesions (WML) on MRI imaging, a significantly higher rate and volume than women with a history of a normotensive pregnancy (17–21%) [6,70,71•]. WML are radiographic findings of hyperintense regions located within the hemispheric white matter on T2 weighted MRI images of the brain [72].…”
Section: White Matter Lesionsmentioning
confidence: 99%
“…First, we did not obtain MRI of lesion reversibility. Although PRES associated with Pe/ES shows maximal reversibility of the brain stem lesions on followup imaging [31,81], adverse sequelae after Pe/ES with imaging presence of cerebral white matter lesions have been reported on longterm follow-up [82]. In addition, RCVS in three-month follow-up angiograms demonstrate complete resolution of vasoconstriction [15,31].…”
Section: Discussionmentioning
confidence: 94%